Architecture of regionalism in the age of globalization : peaks and valleys in the flat world - Lefaivre, Liane; Tzonis, Alexander (New York : Routledge, 2021)
"This book remains the definitive introductory text on the theory and history of regionalist architecture in the context of globalization. It addresses issues of identity, diversity, community, inequality, geopolitics, and sustainability. From the authors who coined the concept of Critical Regionalism, this new edition enhances the understanding of the complex evolution of regionalism and its rival, unchecked globalization. Covering a rich selection of the most outstanding examples of design from all over the world, Liane Lefaivre and Alexander Tzonis present an enlightening, concise historical analysis of the endurance of regionalism and the ceaseless drive for globalization. New case studies include New case studies include current cutting-edge projects in Japan, Africa, China, and the USA. Architecture of Regionalism in the Age of Globalization offers undergraduate and graduate students of architecture, geography, history, environmental studies and other related fields an accessible, vivid, and scholarly perspective of this major conflict as it relates to the design and to the future of the human-made environment"--
Introduction. Universe unbound, the end of regions? -- The origins : regional architecture and the dawn of classical architecture -- Regional into regionalist : dathedrals, palaces, and the case of the Casa dei Crescenzi as a manifesto -- Searching for identity in a flat archipelago of classical garden-villas -- The picturesque revolt : liberty, the merits of chaos, and the 'genius of the place in all' -- From the physiocrats and Rousseau to Goethe's regionalist architecture.
OCLC-licensed vendor bibliographic record.
Keywords: Regionalism in architecture; Architecture and globalization; ARCHITECTURE / General; ARCHITECTURE / History